THE EFFECT OF PRODUCT AND CONSUMER CHARACTERISTICS ON IMPULSE PURCHASING ( STUDY AT FEMALE COSMETIC PRODUCTS ) - Kolondam, Feibe (Universitas Sam Ratulangi, 2016)
Cosmetic products are a set of products that are purchased by women, frequently or unintentionally. Theory related research are impulse purchasing, product and consumer characteristics. The data was collected from 100 respondents they are all female customers that use product cosmetic like compact powder in Manado. This research methodology utilized in this study was survey research and Multiple Linear Regressions Analysis was used to analyze the data. Product characteristic and consumer characteristic are all factors that influence impulse purchasing for female cosmetic products in Manado The result of T-test shows that the independent variables such as product characteristics and consumer characteristics partially have very significant and significant influence. There are three constructive findings that can be concluded from the overall result in this research, which are listed as follow : Product Characteristics and Consumer Characteristics influence the Impulse Purchasing for female cosmetic products in Manado, simultaneously. Product Characteristics influence the Impulse Purchasing for female cosmetic products in Manado, partially. Consumer Characteristics influence the Impulse Purchasing for female cosmetic products in Manado, partially. Â Keywords: product, consumer, characteristic, impulse purchasing